2022
DOI: 10.1111/his.14600
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of pathological techniques to improve lymph node yield from colorectal cancer specimens: a systematic review and network meta‐analysis

Abstract: A number of randomised controlled trials (RCT) have compared different techniques to improve lymph node yield (LNY) in colorectal cancer specimens, but data on comparative effectiveness are sparse. Our aim was to compare the relative effectiveness and rank all available techniques. A systematic search of Embase, Cochrane, PubMed and Scopus was performed for randomised trials. Pairwise was meta-analysis performed if more than two homogeneous studies were available for each comparison. Network meta-analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…[4,5] A recent meta-analysis of randomized controlled trials reported that the use of methylene blue and FD was highly effective for harvesting lymph nodes. [11] However, evidence for the e cacy of the FD method for lymph node retrieval, as in the present study, is mixed. [12,13] In our study, the number of lymph nodes harvested was signi cantly greater in the FD group than in the conventional group, indicating that FD is effective.…”
Section: Discussionmentioning
confidence: 54%
“…[4,5] A recent meta-analysis of randomized controlled trials reported that the use of methylene blue and FD was highly effective for harvesting lymph nodes. [11] However, evidence for the e cacy of the FD method for lymph node retrieval, as in the present study, is mixed. [12,13] In our study, the number of lymph nodes harvested was signi cantly greater in the FD group than in the conventional group, indicating that FD is effective.…”
Section: Discussionmentioning
confidence: 54%
“…Several techniques can be used for lymph node dissection, but they often involve the use of organic solvents or are complex and require more than one day to perform [ 4 , 5 ]. A recent meta-analysis of randomized controlled trials reported that the use of methylene blue and FD was highly effective for harvesting lymph nodes [ 11 ]. However, evidence for the efficacy of the FD method for lymph node retrieval, as in the present study, is mixed [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%